Peranan Dewan Komisaris Terhadap Risk Disclosure Pada Perbankan Umum Di Indonesia - Hendro Lukman; Anto Cahyadi (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
Risk Disclosure in annual reports is needed for third parties to get a complete picture of the annual report and the company. One of those who play a role in the risk disclosure policy is the Board of Commissioners. This study aims to analyze the effect of the size of the Board of Commissioners, Independent Commissioners and Board of Commissioners Meetings on risk disclosure in public banking companies listed on the Indonesia Stock Exchange for the period 2017 – 2021. The research methodology used in this study is a quantitative method. Sampling using purposive sampling method. Valid data is 159 data from 35 general banking companies. Data were processed using multiple regression analysis using IBM SPSS version 25 software. The results showed that the size of the Board of Commissioners, Independent Commissioners, and Board of Commissioners Meetings had a positive effect on Risk Disclosure. The implication of this study is the role of shareholders in selecting and appointing members of the board of commissioners who have competency compatibility with the company's business so that they can provide clear information to stakeholders, as well as minimize the occurrence of information asymmetry between management and shareholders. In addition, investors can also use risk disclosure information to consider the company's business in the future.